Review: Postpartum reproductive disease and fertility in dairy cows - Stephen J. LeBlanc (Animal, 2023)
This paper reviews recent data and concepts on metritis, purulent vaginal discharge (PVD), and endometritis in dairy cows and the ways in which these diseases affect reproductive performance. Metritis is characterized by fetid discharge from the uterus, with or without fever. Purulent vaginal discharge describes exudate that is >50% pus that may be attributable to uterine infection or cervicitis. Endometritis is inflammation of the uterus diagnosed by endometrial cytology with a proportion of neutrophils (typically ≥5%) that is associated with impaired fertility. Metritis and PVD are associated with uterine bacterial dysbiosis: changes in the microbiota to lesser diversity and greater abundance of pathogens, especially Gram-negative anaerobic bacteria, and Trueperella pyogenes in the case of PVD. Metritis is justifiably treated with approved antibiotics but criteria for more selective treatment without loss of performance are emerging. Purulent vaginal discharge is not synonymous with clinical endometritis, and greater precision in terminology is warranted. PVD is likely under-diagnosed and represents an opportunity for improved management in many herds. Endometritis seems in many cases to reflect persistent, dysregulated inflammation, for which the inciting cause is unclear. Postpartum uterine infection and inflammation have harmful effects on oocytes, embryo development, and the endometrium for at least three months, even if the disease is apparently resolved. Emerging concepts of the resolution and regulation of inflammation are promising for the improvement of prevention and therapy of endometritis.